PENDAMPINGAN PEMBUATAN ALAT PERMIANAN EDUKATIF (APE) BONEKA JARI UNTUK MENINGKATKAN KREATIVITAS GURU PAUD KABUPATEN LAMPUNG TIMUR - Elly Purwanti; Khomsiyati , Siti; Hidayat, Rahmat; Fitriyah, Fitriyah (Jurnal Peduli : Jurnal Pengabdian Kepada Masyarakat, 2023)
The creativity of teaching PAUD teachers is the ability of teachers who are always able to develop Educational Game Tools (APE) and are able to create an interesting and calm atmosphere and are able to modify lessons. This assistance aims to produce educational finger puppets to increase the creativity of PAUD teachers. Partner institutions consist of: PAUD Al-Ummi, TPA Baitul Ilmi and SD Islam Darurrohman. The methods used are: (1) Mapping Problems, (2) Activity Preparation (3) Activity Implementation and (4) Evaluation. This activity produces finger puppets as educational games for students in different forms. Furthermore, the results of this assistance will be used in learning in the classrooms of each school.